If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x+2)-3(x-3)=2(x-3)+2(x-2)
We move all terms to the left:
8(x+2)-3(x-3)-(2(x-3)+2(x-2))=0
We multiply parentheses
8x-3x-(2(x-3)+2(x-2))+16+9=0
We calculate terms in parentheses: -(2(x-3)+2(x-2)), so:We add all the numbers together, and all the variables
2(x-3)+2(x-2)
We multiply parentheses
2x+2x-6-4
We add all the numbers together, and all the variables
4x-10
Back to the equation:
-(4x-10)
5x-(4x-10)+25=0
We get rid of parentheses
5x-4x+10+25=0
We add all the numbers together, and all the variables
x+35=0
We move all terms containing x to the left, all other terms to the right
x=-35
| x2+6=3 | | 18-3x+2=2x+5 | | 2*3+x=7 | | x+2*3=7 | | x=2*3=7 | | 2q-16=4-3q | | 3+2(x+5)=13+2x | | 9/2(x+3)=28 | | Z=-4+4i | | (x+1995)(x+1997)(x+1999)(x+2001)+16=0 | | 3k/2+k/5=8 | | (x^2)^2=16 | | F(x)=3^2x+6 | | 7+20+x=180 | | 4x^2-4.5x+1.125=0 | | |w|+5=9 | | 1p+2=p+2 | | 12=x+6-x | | 1600=10x*x | | (12/1)x/12-15=31 | | 7(x-8)=27 | | (4x-12)=120° | | -3(x+4)=2x+37 | | -x+4-(-2)=-8+-x+2 | | (x+(x+4))*6=(x+6)*5 | | X+0.06x=3000 | | N+(n+2)(n+4)=42 | | (x^2)-(3x)-28=171 | | 528=3x+x | | -x+2+(-5)=2+-x | | 129+2x+9=180 | | x-528=3x |